The electric brain : new intelligent agents in esports - Wang, Ziqi (2022)
This thesis studies an emerging technology in artificial intelligence related to esports. Intelligent agents in video games like StarCraft and Dota 2, have become phenomenal in the game communities. Those video games are called esports because they are designed for competition, with a requirement of excellent skill. Creating electronic players in video games is a routine for game developers. However, those agent players in history never astonished human players by reaching high performance in a fair way. The recent agents are created using the same type of AI technology which gave birth to the famous Go program, AlphaGo, and they play the games showing human-like understanding and behaviors. The thesis identifies the generality of those agents by checking the fundamental requirements. The thesis also interprets the impact of these agents to the game community and studies existing cooperation between human and game agents. Two major agent creation procedures were included in comparative analysis and feedbacks to the show matches were collected for case study. The result found the boundaries of the agent's ability and the training procedure, summarized people's attitude, and proposed ways of cooperation and discussion about achieving higher generality.